Pembelajaran Matematika dengan Menggunakan Rel Kereta Bilangan pada Materi Penjumlahan dan Pengurangan Bilangan - Hery Setiyawan (Universitas Pancasakti Tegal, 2017)
This research is to know the influence of mathematics learning by using the number train rail on the addition matter and the reduction of the IV class. This type of research is quantitative. The research method used is Nonequavalent Control Group Design. Research instruments were collected using quiz techniques. The research location is SDN Made 1 No.475 Surabaya Jl. Made Raya No. 31-33. The subjects of the study were students of class IV-A and IV-B. The results showed that there was an influence between the experimental group and the control group. There is a difference between the learning that uses the medium of the railway train of numbers with the learning using the number line. From the number of percentage obtained from the analysis of student response data that exceeds the specified standard, it can be said that the use of medium rail train number in class IV gets a positive response.